(untitled) (Per Musi, 2011)
Baroque religious art built true machines capable of amazing those who approached them. The intent behind such devices was to convert and amaze the faithful, as a kind of “bait” which could attract them, and make them take into account the teachings of the Catholic Church. In this sense, we seek to identify in religious painting, woodcarving and music of colonial Minas Gerais (Brazil) some artifices employed to provoke wonder and teach the faithful.